Prediksi Pemberian Rekomendasi Kenaikan Pangkat PNS Menggunakan Metode Naïve Bayes - Desi Irfan; Irwan Daniel; Adam Sagara; Zakarias Situmorang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
A civil servant or civil servant (English: civil servant, Dutch: ambtenaar) is a person employed by a government agency to provide public services. As a profession, civil servants are positions that are pursued through career paths and not based on general elections involving the people's vote. Quoted from the Regulation of the Head of BKN No. 35 of 2011 concerning Guidelines for the Preparation of PNS Careers, the career pattern of civil servants is arranged based on the principles of certainty, professionalism, and transparency. One of the requirements to achieve the desired career is through the promotion process. The promotion or class of a civil servant cannot be separated from the recommendation of the leadership. A leader in providing recommendations must look at several important points that must be possessed by employees who will be given recommendations such as Attendance, Integrity, Cooperation and Insight or Knowledge. In the process, there are still problems in terms of technical and effectiveness because manual assessments sometimes still assess subjectively. Therefore, a study was carried out for the classification of the determination of the status of giving recommendations using the Naïve Bayes method. Naive Bayes is one method of probabilistic reasoning. The Naive Bayes algorithm aims to classify data in certain classes, then the pattern can be used to estimate the employee who will be given a recommendation, so that the leader can make a decision to give recommendation or not to the employee